Synthesis of Zirconia Doped Molybdenum Oxide as Efficient Catalysts for Ultrasound Assisted Synthesis of Substituted Pyrazoles - A. Muftah, Amal; A. Waghmode, Shobha; R. Gadale, Sharda (Asian Journal of Chemistry, 2021)
To explore green methodology for the synthesis of mixed oxide, its catalytic activity and temperature stability of series of ZrO2/MoO3 and ZrO2 were prepared by sol-gel method and characterized by XRD, FT-IR, X-ray photoelectron spectroscopy (XPS), temperature programmed Desorption (TPD), Raman spectroscopy and transmission electron microscopes (TEM). These mixed oxides were showed high stability with nanocrystalline nature. Due to highly acidic nature of the catalysts, ultra sound assisted synthesis of substituted pyrazoles was carried out successfully with high yield. The reaction was carried out in solvent free medium, which showed green approach and energy saving reaction. Condensation of dibenzoyl methane and hydrazine to form substituted pyrazoles with 97.7% yield. The acid strength and acid amount of synthesized catalysts were determined by temperature programmed desoprtion (TPD), incorporation of zirconia into the molybdenum, network has changed its surface acid properties due to the Zr2+ and Mo6+ ions. After addition of ZrO2 on MoO3, it showed weak and strong acid sites.